Analysis Of The Preparation Of Financial Reports Based On Accounting Standards For Financial Entities Without Public Accountability No. 5 Of 2009 At The Princess Hotel In Bengkulu - Lensa Odios; Ahmad Soleh; Herlin Herlin (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2023)
This research aims to analyze the application of SAK ETAP No.05 of 2009 concerning profit and loss reports at the Princess Bengkulu Hotel. The aim of this research is to determine the suitability of implementing SAK ETAP No. 05 of 2009 concerning profit and loss reports at the Princess Benkulu Hotel. The data analysis used is comparative descriptive, namely a research method that compares a valid theory with events that occur in the field. The results of this research indicate that the Princess Bengkulu Hotel specifically has not prepared a profit and loss report in accordance with SAK ETAP No. 05 of 2009, but in the profit and loss report of the Hotel Princess Bengkulu, 80% of the components are in accordance with SAK ETAP No. 05 of 2009 which applies. These components include income, expenses, profit or loss, tax expense, net profit or loss.